DESIGN OF TOTAL DISSOLVE SOLID (TDS) MEASURING USING CONDUCTIVITY SENSOR AND TEMPERATURE SENSOR DS18B20 - Widodo; Stiyawan, Eko Agus (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
TDS meter is a measure of the conductivity of solutes in liquids, this tool is often used as an important component in determining water quality before use. There are still several components to be examined beside TDS, one of which is temperature. Temperature is an important component to measure the feasibility of water. Temperature measuring devices can be used to find out how much the temperature of the liquid being measured. The TDS meter that is already in the general public can only be used to find out the TDS. So, if people want to measure other components such as temperature, a thermometer is needed to measure it, of course this becomes inefficient and requires a higher cost because if you want to measure other components, the public must buy another measuring instrument. Therefore, on this occasion to make measurement tools become more efficient, the writer will design a measuring instrument that can be used to measure 2 components at once, namely a TDS meter and a thermometer designed in one device. TDS meter uses a conductivity sensor and a thermometer uses a DS18B20 waterproof temperature sensor.